Karakteristik Cookies Tepung Umbi Lokal dan Tepung Jewawut dengan Penambahan Kuning Telur - Dyah Setyawati; Dedin Finatsiyatull Rosida; Luqman Agung Wicaksono (Universitas Islam Raden Rahmat, Malang, 2024)
Cookies are small sweet snacks with a crunchy and hollow texture. This research aims to determine the characteristics of cookies from local tuber flour and millet flour with egg yolk concentration. The research design used was a two-factor completely randomized design. Factor I, type of local tuber flour (kimpul, white yam, yellow sweet potato): millet flour (70:30) and factor II, egg yolk concentration (10%, 12%, 14%). The results of the analysis found that the treatment of kimpul flour and millet flour (70:30) with the addition of 10% egg yolk concentration was the best treatment. The characteristics of the cookies produced are a moisture content of 4.90%, ash content of 0.87%, fat content of 20.92%, and a breaking strength of 9.3 N. The results of the hedonic test show an overall average color of 4.25 (like), taste 3.90 (like), aroma 3.95 (like), texture 3.85 (like).